WNT signaling in neuronal maturation and synaptogenesis - Rosso, Silvana B.; INESTROSA, NIBALDO C.; Rosso, Silvana B. (Frontiers in Cellular Neuroscience, 2013)
The Wnt signaling pathway plays a role in the development of the central nervous system (CNS) and growing evidence indicates that Wnts also regulates the structure and function of the adult nervous system. Wnt components are key regulators of a variety of developmental processes, including embryonic patterning, cell specification, and cell polarity. In the nervous system, Wnt signaling also regulates the formation and function of neuronal circuits by controlling neuronal differentiation, axon outgrowth and guidance, dendrite development, synaptic function and neuronal plasticity. Wnt factors can signal through three very well characterized cascades: canonical or β-catenin pathway, planar cell polarity pathway and calcium pathway that control different processes. However, divergent downstream cascades have been identified to control neuronal morphogenesis. In the nervous system, the expression of Wnt proteins is a highly controlled process. In addition, deregulation of Wnt signaling has been associated with neurodegenerative diseases. Here, we will review different aspects of neuronal and dendrite maturation, including spinogenesis and synaptogenesis. Finally, the role of Wnt pathway components on Alzheimer’s disease will be revised.